PM2.5, respiratory health risk and IL-6 levels among workers at a modern bus terminal in Kuala Lumpur - Rasdi, Irniza; Ghazali, Nur Izzati; Zainal Abidin, Emilia; Syed Ismail, Sharifah Norkhadijah; Praveena, Sarva Mangala (Community Health Society Malaysia, 2014)
Background: A recent study in Taipei found that the levels of PM2.5 in a bus terminal were 1.6 to 1.8 times higher than in the urban background and were far above the permissible exposure limits (PEL). Since there has been no such research conducted in Malaysia, the present study aims to assess the level of PM2.5 in a new bus terminal in Kuala Lumpur and to measure the possible respiratory health risk of the workers.